Assessment of oral health status of Santal (Tribal) children of West Bengal - Shyamapada Mandal; Chiranjit Ghosh; Subrata Sarkar; Jayita Pal; Sudipta Kar; Badruddin Ahmed Bazmi (Wolters Kluwer Medknow Publications, 2015)
Context: Santal is the third largest tribal community of India leading a very poor standard of education and life style. There are, however, few population-based studies evaluating the oral health status among Santal children in West Bengal. Aims: The aim of the study was to evaluate the oral health status of Santal children of West Bengal by assessing prevalence of dental caries and inflammatory condition of gingival. Settings and Design: Santal children aged between 2-14 years (N = 1205) were randomly selected from different Santal communities of West Bengal for this study. The children were divided into three different groups according to dentition. Materials and Methods: Caries for permanent dentition Decayed Missing Filled Tooth (DMFT), for deciduous dentition decayed extracted filled (def index was used. For mixed dentition DMF and def was measured respectively and then added together. Inflammatory condition of gingival was assessed by papillary marginal attachment (PMA) index. Statistical Analysis Used: the data was analyzed statistically by SPSS software version 11. Results: The study showed there was no significant difference (P > 0.05) between the average decayed extracted filled teeth (deft)/DMFT for boys and girls in deciduous and permanent dentition. But in mixed dentition this value for the boys was significantly higher (P < 0.001) than girls. 'Z' values were found to be non significant when compared mild, moderate and severe gingivitis between boys and girls in each dentition group, but mild gingivitis significantly increases from deciduous dentition to mixed to permanent dentition (P <0.001).